FILSAFAT PANCASILA DALAM PERSEPEKTIF HINDU - Kartika, Ni Gusti Ayu (Institut Hindu Dharma Negeri Denpasar, 2018)
Pancasila is not just born, but through a very thorough planning process and reviewed by National figures through the session of the Preparatory Committee for the Preparation of Independence (BPPK). Pancasila as the foundation of the philosophy of the state of the Republic of Indonesia has the composition of five precepts which is a unity and unity and has the nature of the unity of the absolute, which is the nature of the monodualist nature as individual beings as well as social beings, and position as a personal being that stands alone and simultaneously also as a creature of God. The consequences of Pancasila as the basis of the state of Indonesia are all aspects in the administration of the state covered by the values of Pancasila which is the human nature that monodualis.